2019
DOI: 10.1021/acs.iecr.8b05848
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Phosphonium-Based Ionic Liquid to the Separation of Platinum Group Metals from Automobile Catalyst Leach Liquor

Abstract: The recovery of platinum group metals (PGMs) from automotive exhaust catalysts is important, and hydrometallurgical extraction is an effective approach. In the present study, a newly designed phosphonium-based ionic liquid (IL) was applied to the separation and recovery of PGMs from an automobile catalyst leach liquor in conjunction with varying pH levels. This IL, trioctyldodecyl phosphonium chloride (P 8,8,8,12 Cl), allows quantitative extraction of Pd(II) at any HCl concentration, with almost 80% removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…The metal-chloro complex species, which depends on the HCl concentration, determines the extraction mechanism. As reported in our previous study, extraction of FeCl 3 , which is the dominant Fe species in the aqueous feed solution, occurs by ion association of the IL cation with [FeCl 4 ] − (Firmansyah et al, 2019).…”
Section: Extraction Of the Metal Ions Contained In The Leachatementioning
confidence: 66%
See 4 more Smart Citations
“…The metal-chloro complex species, which depends on the HCl concentration, determines the extraction mechanism. As reported in our previous study, extraction of FeCl 3 , which is the dominant Fe species in the aqueous feed solution, occurs by ion association of the IL cation with [FeCl 4 ] − (Firmansyah et al, 2019).…”
Section: Extraction Of the Metal Ions Contained In The Leachatementioning
confidence: 66%
“…In our previous study, we found that Fe(III) can be stripped from the P 8,8,8,12 Cl phase by reducing Fe(III) to Fe(II) using Na 2 SO 3 (Firmansyah et al, 2019). About 90% of Fe can be removed from the metal-loaded IL phase by contact with 1.2 mol L −1 Na 2 SO 3 at 303 K, while Pt and Pd remain in the IL phase (Table 3).…”
Section: Stripping Of the Metals From The Il Phasementioning
confidence: 98%
See 3 more Smart Citations